2022
DOI: 10.3389/fbioe.2022.933901
|View full text |Cite
|
Sign up to set email alerts
|

New Hope for Treating Intervertebral Disc Degeneration: Microsphere-Based Delivery System

Abstract: Intervertebral disc (IVD) degeneration (IVDD) has been considered the dominant factor in low back pain (LBP), and its etiological mechanisms are complex and not yet fully elucidated. To date, the treatment of IVDD has mainly focused on relieving clinical symptoms and cannot fundamentally solve the problem. Recently, a novel microsphere-based therapeutic strategy has held promise for IVD regeneration and has yielded encouraging results with in vitro experiments and animal models. With excellent injectability, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 156 publications
(215 reference statements)
0
13
0
Order By: Relevance
“…200,201 Different manufacturing processes can produce microspheres with different structural characteristics to allow microspheres to be used in different medical applications. 202 Materials for the preparation of microspheres include glass (such as that made of silicate, borate, or phosphate), ceramics, and polymers. Polymer-based porous microspheres have been extensively investigated for drug release and as delivery vehicles for other biological components.…”
Section: Microspheresmentioning
confidence: 99%
See 1 more Smart Citation
“…200,201 Different manufacturing processes can produce microspheres with different structural characteristics to allow microspheres to be used in different medical applications. 202 Materials for the preparation of microspheres include glass (such as that made of silicate, borate, or phosphate), ceramics, and polymers. Polymer-based porous microspheres have been extensively investigated for drug release and as delivery vehicles for other biological components.…”
Section: Microspheresmentioning
confidence: 99%
“…Commonly used methods for microsphere preparation include evaporation of emulsification solvent, phase separation, spray drying, electro‐spraying, and microfluidic methods 200,201 . Different manufacturing processes can produce microspheres with different structural characteristics to allow microspheres to be used in different medical applications 202 …”
Section: Further Delivery Strategiesmentioning
confidence: 99%
“…Polymers, including artificial polymers and natural polymers, are used to prepare microspheres due to their biocompatibility and easy modification [39]. At present, several methods, including emulsification and electrohydrodynamic spraying technology, have been developed to prepare microspheres.…”
Section: Polymers For Microspheresmentioning
confidence: 99%
“…encapsulation rate and excellent slow-release properties conferred by the porous structure, coupled with good surface adhesion for cell immigration, have led to the gradual emergence of microspheres as the carrier of choice in the field of tissue engineering (Guo et al, 2022). In order to achieve long-term delivery and avoid leakageassociated complications, stimulus-responsive composite hydrogels have been employed.…”
mentioning
confidence: 99%
“…The microsphere is a class of three-dimensional spherical structures with an average particle size of 1–1000 μm that could be used in cell carrying and biomedical substance delivery. Guo et al recently reviewed the use of various microspheres for disc regeneration and clearly demonstrated that the high encapsulation rate and excellent slow-release properties conferred by the porous structure, coupled with good surface adhesion for cell immigration, have led to the gradual emergence of microspheres as the carrier of choice in the field of tissue engineering ( Guo et al, 2022 ). In order to achieve long-term delivery and avoid leakage-associated complications, stimulus-responsive composite hydrogels have been employed.…”
mentioning
confidence: 99%